Analysis of lipid profile in cancer patients, smokers, and nonsmokers - A Vikramsimha Reddy; Lakshmi Keerthana Killampalli; A Ravi Prakash; Sushma Naag; G Sreenath; Sunil Kumar Biraggari (Wolters Kluwer Medknow Publications, 2016)
Background: Lipids play an important role in maintaining the cell membrane integrity. Lipid profile is a panel of blood tests that serve as an initial medical screening for abnormalities in lipids and approximate risk for cancer, cardiovascular diseases, pancreatitis, etc., The present study evaluates the alterations in lipid profile in cancer patients, smokers, and nonsmokers and aims to achieve a correlation between them. Materials and Methods: The study is an in vitro type of cross-sectional study with 25 oral cancer patients, 25 chronic smokers (habit persisting for 15 years or more), and 15 nonsmokers as control group. Blood samples had been collected, and triglycerides (TGs), total cholesterol (TC), high-density lipoprotein (HDL), very low-density lipoprotein (VLDL), and low-density lipoprotein (LDL) were analyzed using a lipid profile kit and an autoanalyzer. The results were analyzed using the unpaired t-test and ANOVA test (P < 0.05). Results: There was a significant increase in TC, TG, LDL, and VLDL and decrease in HDL in the smokers group when compared to the controls (P < 0.05). A significant increase in LDL, but a decrease in values of HDL, VLDL, TG, and TC was observed in the cancer patients group when compared to the controls (P < 0.05). Conclusion: There is an inverse relationship between serum lipid profile in smokers and cancer patients. The decrease in lipid profile in cancer patients might be due to their increased utilization of lipids by neoplastic cells in membrane biogenesis. Therefore, a decrease in lipid profile in smokers can be assumed that they might be more prone to develop cancerous conditions.